Allergic tonsillar polyp: an uncommon lesion - Vare, Anil A.; Vare, Rena A.; Nair, Sanjana U. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Tonsils are not so commonly affected by allergic lesions or polyps. In this study we attempt to elucidate the nature of tonsillar polyps. Methods: The present study is a hospital based retrospective clinicopathological study in which a total of nine cases whose histopathological slides were reviewed and patient follow up was obtained. Results: There were 5 males and 4 females between the age group of 15 to 30 years. Most of the cases presented with complaints of repeated throat pain, difficulty swallowing, foreign body sensation in throat and dry irritating cough. On examination a pedunculated sessile mass in seen protruding from the surface of the palatine tonsil usually unilateral. The clinical differentials included were tonsillar lipoma, haemangioma, lymphangioma, inclusion cyst and neoplasm. Based on histopathological examination following tonsillectomy with polypectomy a conclusion of allergic polyp was made and clinical follow up information of patients were obtained post-operatively. In this series we examine the clinicopathological features of polypoidal lesions of tonsils whose specific diagnosis was obtained after histopathological examination. Conclusions: A histopathological examination must be obtained in all cases of tonsillar polyps for proper post-operative management.